Edukasi Anti Korupsi Calon Guru SD/MI (Sebagai Upaya Untuk Internalisasi Nilai Anti Korupsi Dalam Pembelajaran) - Ulfa, Nanik; meditama, Ratna fajarwati; salim; firdausi, rofiqoh (Universitas Nusantara PGRI Kediri, 2022)
Corruption is a big problem in Indonesia. According to a survey by the transparency agency, Indonesia is in the sixth most corrupt position in the world. Indonesia's human resources are still not good. To overcome these problems, cooperation with all parties is needed. Eradication of corruption must be carried out on the community as a whole. In this case, education also has an important role in nation building, one of which is by forming a generation of people who have an anti-corruption spirit. These activities must be carried out in an applicative manner so that students can understand and apply them in everyday life. One form of activity to assist the government in eradicating corruption through education, the PAKU (Anti-Corruption Study Center) institution in collaboration with the PGMI Study Program held an Anti-Corruption Education activity for prospective MI teachers.